How does traditional chinese medicine treat attention deficit hyperactivity disorder-A different understanding and treatment strategy - Sai Zhao; Yuanxiong Deng; Zijia Chen; Sumei Wang (Open Journal of Orthopedics and Rheumatology - Peertechz Publications, 2023)
Attention Deficit Hyperactivity Disorder (ADHD) is a common neurodevelopmental disorder, and the incidence in children is increasing year by year. The modern medical field lacks long-acting drugs for the treatment of ADHD and there is an urgent need to investigate new therapeutic drugs or complementary and alternative therapies. Recent studies have found that Traditional Chinese Medicine (TCM) has the advantages of individualization, precise efficacy and minimal side effects in improving attention deficit hyperactivity disorder. This paper reviews the progress of Chinese medicine in the treatment of ADHD in terms of its understanding of the etiology and pathogenesis of ADHD, treatment according to pattern identification and Chinese medicinal preparations.